2018
DOI: 10.1186/s41256-018-0068-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between sporting event attendance and self-rated health: an analysis of multiyear cross-sectional national data in Japan

Abstract: BackgroundThis study examined the extent to which sporting event attendance is associated with self-rated health. Drawing from an economic model of health production and psychological research on the health benefits of psychosocial resources, sporting event attendance was hypothesized to have a positive relationship with self-rated health.MethodsA two-level multilevel ordered logistic regression was used to analyze multiyear cross-sectional data collected from national surveys in Japan.ResultsThe results demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Third, by collecting data from older adults living in nearly 70 counties in the United States, the present research offers evidence that has high generalizability in this specific country context. In addition, given previous research indicating that spectator sports can be a setting to promote mental health and well-being in other countries, such as Australia (Doyle et al, 2016), the United Kingdom (Clark et al, 2015), and Japan (Inoue, Sato, & Nakazawa, 2018; Kawakami et al, 2017), it can be assumed that the relationships identified in this research are applicable beyond the United States. Nevertheless, to further understand the role of spectator sports in older adults’ lives, it is important that future researchers will engage in multicounty investigations to test our structural model using data from older adults living in various countries and determine whether model modifications are needed to take into account country-specific characteristics (e.g., economic and social factors, popularity of spectator sports, availability of other social activities).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Third, by collecting data from older adults living in nearly 70 counties in the United States, the present research offers evidence that has high generalizability in this specific country context. In addition, given previous research indicating that spectator sports can be a setting to promote mental health and well-being in other countries, such as Australia (Doyle et al, 2016), the United Kingdom (Clark et al, 2015), and Japan (Inoue, Sato, & Nakazawa, 2018; Kawakami et al, 2017), it can be assumed that the relationships identified in this research are applicable beyond the United States. Nevertheless, to further understand the role of spectator sports in older adults’ lives, it is important that future researchers will engage in multicounty investigations to test our structural model using data from older adults living in various countries and determine whether model modifications are needed to take into account country-specific characteristics (e.g., economic and social factors, popularity of spectator sports, availability of other social activities).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…This finding is consistent with our hypothesis and other studies discussed previously. 2,3,7 An additional finding from our study is that Saints football games do not exclusively affect average hospital admissions on game days, but this impact extends to the 24 hours after the game as well. Specifically, on the post-game day following a Saints victory, we found an 18.2% increase in the average number of admissions compared to the average census Nguyen, VD following a Saints loss.…”
Section: Discussionmentioning
confidence: 53%
“…In Japan, Inoue et al reported a positive association between sport spectatorship and the perception of general health through their analysis of 12-year cross-sectional data collected from national surveys. 2 Specifically, in comparison to those who did not attend any sporting event in a year, those who did were 33% more likely to report a higher level of self-rated health. The study suggests that attending sporting events is an important nonexercised form of leisure that might produce psychosocial resources and contribute to good health.…”
Section: Introductionmentioning
confidence: 97%
“…Since the publication of Inoue, Berg, et al (2015), several studies have been published in both sport management (e.g., Collins & Heere, 2018;Schlegel et al, 2017;Taks et al, 2016) and non-sport management journals (e.g., Inoue et al, 2018;Lera-López et al, 2020;Wann et al, 2017) to explore the relationship between spectator sport and population health. In relation to the physical well-being domain of population health, an analysis of multi-year secondary data in Japan found that attendance at sport events was positively associated with individuals' subjective perceptions of physical well-being as measured by a self-rated health scale (Inoue et al, 2018).…”
Section: Spectator Sport and Population Health Researchmentioning
confidence: 99%